PENGENDALIAN PERSEDIAAN OBAT GENERIK PADA INSTALASI FARMASI RSUD LAKIPADADA DI TANA TORAJA - Pundissing,, Rati (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2019)
The importance of a hospital have a good medicine control that pharmaceuticals are not excessive or shortage. The study aims to: (1) describe the control of generic medicine supply at the pharmacy unit that causes stock out; (2) determine whether ABC, EOQ, and ROP control systems can be used to avoid stock out; and (3) determine the level of safety stock that needs to be stored in the warehouse to avoid stock out. The research can be categorized as a qualitative and quantitative study. It used primary data obtained from in-depth interviews and secondary data obtained from document review. The results reveal that: (1) stock control that causes stock out is the stock opname. (2) stock control with ABC, EOQ, and ROP analysis helps the management to plan medicine supply and to avoid stock out. The ABC analysis shows that 36 kinds (12%) of generic medicine are in Group A, which use budget of 69.60% from the total budget. Group B consists of 52 kinds (17.33%) of generic medicine, using budget of 20.39% from the total budget; while Group C  consists of 212 kinds (70.67%) of generic medicine using budget of 10.01% from the total budget. The maximum order for generic medicine in Group A should consist of 2-5265 items; while The maximum order for generic medicine in Group B should consist of 6-6879 items. The maximum order for generic medicine in Group C should consist of 1-5503 items. Reorder time for generic medicine in Group A starts from 1 to 2315 items, while reorder time for generic medicine in Group B starts from 2-1663 items. Reorder time for generic medicine in Group C starts from 1-916 items. (3) to avoid stock out, safety stock in the warehouse should be 3-1442 items for group A, 1-1036 items for Group B, and 3-570 items for Group C.